2006
DOI: 10.4049/jimmunol.176.4.2161
|View full text |Cite
|
Sign up to set email alerts
|

A Major Lung CD103 (αE)-β7 Integrin-Positive Epithelial Dendritic Cell Population Expressing Langerin and Tight Junction Proteins

Abstract: Dendritic cells (DC) mediate airway Ag presentation and play key roles in asthma and infections. Although DC subsets are known to perform different functions, their occurrence in mouse lungs has not been clearly defined. In this study, three major lung DC populations have been found. Two of them are the myeloid and plasmacytoid DC (PDC) well-characterized in other lymphoid organs. The third and largest DC population is the integrin αE (CD103) β7-positive and I-AhighCD11chigh-DC population. This population was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
282
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 435 publications
(303 citation statements)
references
References 65 publications
15
282
1
5
Order By: Relevance
“…In the mouse, intraepithelial CD11b À CD103 1 lung DC have been shown to express claudin-1, claudin-7 and zonula-2 proteins to form tight junctions with neighboring airway epithelial cells. This could explain how DC sample the airway lumen without disturbing the epithelial barrier function [27]. A similar model has been proposed in the gut as well as in the skin, where Langerhans cells extend dendrites just underneath the stratum corneum [28,29].…”
Section: Functional Specializations Of Lung DC Subsetsmentioning
confidence: 61%
“…In the mouse, intraepithelial CD11b À CD103 1 lung DC have been shown to express claudin-1, claudin-7 and zonula-2 proteins to form tight junctions with neighboring airway epithelial cells. This could explain how DC sample the airway lumen without disturbing the epithelial barrier function [27]. A similar model has been proposed in the gut as well as in the skin, where Langerhans cells extend dendrites just underneath the stratum corneum [28,29].…”
Section: Functional Specializations Of Lung DC Subsetsmentioning
confidence: 61%
“…We chose Siglec-F as a potential marker amenable to this flow-based approach since it has documented to be present on the surface of eosinophils and alveolar macrophages (Sung et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Neither population expressed high levels of MHC II, CD86, or CD40 when compared to the relevant isotype controls, suggesting that these populations did not include conventional Siglec-F − CD11c + dendritic cells (Sung et al 2006) (TS Kim, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing Langerin-EGFP knockin mice it became apparent that the majority of blood-derived CD8 1 DC in the thymus, spleen, cutaneous LN (CLN) and mesenteric LN also express lower levels of Langerin, depending on the genetic background (Table 2) [30,38,39]. Langerin 1 CD8 À (CD103 1 CD11b À ) DC have also been described in the lung specifically localized at the basal lamina of the bronchial epithelia and arterioles of the lung [40]. Initial studies with the Dutch and French Langerin-DTR-EGFP models demonstrated that DT treatment efficiently ablated LC in the epidermis, as well as LC and blood-derived CD8 1 Langerin lo DC in the CLN.…”
mentioning
confidence: 99%
“…Both cell types maintain their phenotype in the skin and CLN. Interestingly, Langerin 1 dDC are phenotypically very similar to Langerin 1 DC populations found in the lung, and it is yet unclear whether these two populations are mutually exclusive or together constitute a Langerin 1 interstitial DC subset [36,40]. Recent experiments demonstrate that clearance of influenza virus from the lung depends on this migratory Langerin 1 DC subset [43].…”
mentioning
confidence: 99%